Peran Bantuan Pendidikan dalam Meningkatkan Retensi Mahasiswa dari Keluarga Kurang Mampu - Safinatun Naja Assuffie; Gina Indah Permata Nastia (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2026)
Higher education serves as an instrument for developing the quality of human resources (HR). Therefore, the issue of sustainability in higher education requires proper attention and management from various stakeholders, including the government, higher education institutions, and the community. However, not all students share the same financial circumstances when pursuing higher education, particularly those from underprivileged families who often face limitations in meeting educational needs. These conditions potentially affect the sustainability of their studies and increase the risk of discontinuing education before completion. Consequently, this study aims to examine the role of educational assistance in improving the retention of students from underprivileged families. This research employs a qualitative approach through a literature review of various relevant scientific sources. The study seeks to explore the correlation between student retention and educational assistance in Indonesia, as well as to analyze the extent to which such assistance plays a role in reducing student dropout rates. The findings indicate that educational assistance plays a positive role in supporting study sustainability by providing financial support that helps meet academic requirements and living expenses during the course of study. Furthermore, educational assistance also impacts the improvement of students' learning motivation and self-confidence in completing their higher education. Thus, educational assistance is one of the contributing factors to increasing the retention of students from underprivileged families in higher education.